Tourist engagement and loyalty: gender matters? - Rasoolimanesh, S. Mostafa; Khoo-Lattimore, Catheryn; Md Noor, Shuhaida; Jaafar, Mastura; Konar, Rupam (Current issues in tourism, 2021)
This study aims to compare the effects of several dimensions of tourist engagement, including enthusiasm, attention, absorption, interaction, and identification on loyalty across male and female tourists. A total number of 210 questionnaire were completed from tourists visiting Kinabalu National Park in Sabah, Malaysia. This study uses both partial least squares-structural equation modeling and fuzzy-set qualitative comparative analysis to elucidate further insights. The results showed significant differences between the effects of attention on loyalty, with this effect being much stronger for male tourists. However, the findings demonstrated more complex sufficient configurations and heterogeneity among female tourists for achieving high levels of loyalty. This study makes a significant contribution to the research literature by comparing the engagement and loyalty of male and female tourists toward a destination, having identified greater heterogeneity among female tourists. This study has a number of practical implications for local authorities aiming to improve loyalty among male and female tourists.